Socio‐economic status and mortality in people with type 1 diabetes in Scotland 2006–2015: a retrospective cohort study. Issue 12 (3rd February 2020) - Campbell, R. A. S.; Colhoun, H. M.; Kennon, B.; McCrimmon, R. J.; Sattar, N.; McKnight, J.; Wild, S. H; ,
Abstract: Aims: To describe the association between socio‐economic status and mortality in a nation‐wide cohort of people with type 1 diabetes in Scotland and to compare patterns over time and with the general population. Methods: A retrospective cohort study was performed using data for people with type 1 diabetes from a population‐based register linked to mortality records. Socio‐economic status was derived from quintiles of an area‐based measure: the Scottish Index of Multiple Deprivation. Sex‐specific directly age‐standardized mortality rates for each Scottish Index of Multiple Deprivation quintile and rate ratios comparing the most vs least deprived quintile were calculated for two time periods: 2006–2010 and 2011–2015. Data for the population without type 1 diabetes between 2011 and 2015 were available for comparison. Results: Data for 3802 deaths among 33 547 people with type 1 diabetes were available. The age‐standardized mortality rate per 1000 person‐years decreased over time (from 2006–2010 to 2011–2015) for men and women with type 1 diabetes: 24.8 to 20.2 and 22.5 to 17.6, respectively. Mortality in populations with and without type 1 diabetes was generally higher for men than women and was inversely associated with socio‐economic status. Rate ratios for the most vs least deprived groups increased over time among people with type 1 diabetes (men: 2.49 to 2.81; women: 1.92 to 2.86) and were higher than among populations without type 1 diabetes in 2011–2015 (men: 2.06; women: 1.66). Conclusions: Socio‐economic deprivation was associated with a steeper mortality gradient in people with type 1 diabetes than in the population without type 1 diabetes in Scotland. Age‐standardized mortality has decreased over time but socio‐economic inequalities may be increasing. What's new?: The socio‐economic gradient in mortality within the general population and in type 2 diabetes is established. Scandinavian population‐based cohort studies of people with type 1 diabetes have reported an inverse association between socio‐economic status and mortality but there are no contemporary data for the UK. This study found that socio‐economic deprivation was associated with higher mortality in people with type 1 diabetes in Scotland, that the effect of deprivation was larger than in the general population and that inequalities appear to be widening over time. Effective interventions to reduce socio‐economic inequalities in outcomes of type 1 diabetes are required.